Forced Collection of Covid-19 Corpse From the Hospital - Petrus, Asan; Sembiring, Erwin; Priatna, Reja; Marissa (Talenta Publisher, 2022)
The Covid-19 pandemic has been ongoing for almost two years and the number of the new cases is still happening and without any sign of it ending. The number of cases has almost reached four million cases (3,854,354 cases) as of August 15, 2021. Other reasons contributing to this other than the lack health protocol implementation are community activities involving large crowds and incorrect handling of corpses who died due to Covid-19 in the community like forced retrieval of Covid-19 corpse from the hospital. For this reason, the importance of this discussion is to increase the public understanding of the legal aspects of forced retrieval of COVID-19 bodies from hospitals, the risk of transmission due to forced retrieval of COVID-19 bodies from hospitals, to reduce transmission of COVID-19 in the midst of society. The method is implemented in the form of a live broadcast discussion via Instagram from RSUPHAM Medan with the topic